The Interactive Meaning of a Movie Poster: a Multimodality of Spiderman: No Way Home - Shella Puspita Dewi; Khristianto Khristianto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
This study aims to disclose the interpersonal meaning in movie posters. This is a semiotic study, applying Royce's (2001) intersemiotic complementarity framework. It is to analyze visual and verbal codes in the posters. The poster is taken from the official website of Marvel Studio. They are used as a medium for advertising the products. Based on the analysis, it can be identified that the visual contact is straighforward creating a demanding pose, a close-up mode presenting an emotional expression instead of the covered face, the frontal view emphasizing the bond of the character to the viewers, its eye-level presentation creating his equality to the on-lookers. All of this demanding pose was made clear by the situation informed by the verbal elements, that Spiderman had no way home. It is also a preview of the plot of the movie in this sequel. Thus, both semiotic elements in the poster have produced a unity of meaning, which puts the superhero as a part of the society in general, especially where he lives; he is not a different human being in spite of the super power he holds.